Relationship between declining glomerular filtration rate and measures of cardiac and vascular autonomic neuropathy. Issue 12 (December 2016) - Clyne, Naomi; Hellberg, Matthias; Kouidi, Evangelia; Deligiannis, Asterios; Höglund, Peter
Abstract: Aim: Cardiac and vascular autonomic neuropathy contributes to increased morbidity and mortality in patients with chronic kidney disease. The aim of this study was to analyze the effects of a decline in glomerular filtration rate (GFR) on heart rate variability (HRV) and nocturnal blood pressure dipping. Methods: This cross‐sectional study comprises 124 patients (46 women, 78 men; age 66 ± 14 years) with chronic kidney disease (CKD) 3–5, not on renal replacement therapy. GFR was measured with iohexol clearance, HRV with 24 h Holter electrocardiogram (ECG) and nocturnal dipping with 24 hour ambulatory blood pressure. Results: The GFR was 22.5 ± 8.5 mL/min per 1.73 m 2 . The main finding was a significant curvilinear association between the 24 h standard deviation of NN interval (24SDNN) in the HRV analysis and GFR ( P  = 0.01), logGFR ( P  = 0.006), diabetes mellitus ( P  = 0.05) and beta blocker treatment (0.03), respectively. The effect of diabetes mellitus on 24SDNN corresponded to a decline in GFR from 30 to 12 mL/min per 1.73 m 2 . There were significant curvilinear associations between systolic nocturnal dipping ( P  = 0.02) and diastolic nocturnal dipping ( P  = 0.05), respectively, and diabetes mellitus but not with GFR or logGFR. Conclusion: In conclusion, cardiac sympathetic overdrive and decreased vagal control appear during CKD 4 and 5. The association with GFR is curvilinear. Diabetes mellitus was significantly associated with both cardiac and vascular autonomic neuropathy, as measured by heart rate variability and nocturnal blood pressure dipping, respectively. Knowing that arrhythmias, often due to sympathetic hyperactivity, are an important cause of sudden death in the dialysis population, this study contributes important knowledge on possible intervention thresholds. Summary at a Glance: Study on 124 patients with CKD with iohexol GFR, 24 hour ECG monitoring, and 24 hour ambulatory BP monitoring showing a curvilinear relationship between GFR and heart rate variability. The findings provide insight into the association of kidney function with sympathetic activity that could have an influence on CVD outcomes.